1994
DOI: 10.1159/000261618
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro Mouth Model to Test Antiplaque Agents: Preliminary Studies Using a Toothpaste Containing Chlorhexidine

Abstract: The development of an in vitro model simulating the oral cavity has allowed the antiplaque activity of a toothpaste containing 0.004% chlorhexidine to be tested. The model is based on the continuous irrigation of bovine tooth samples with artificial saliva. Scanning electron microscopy showed homogeneous colonization of monobacterial plaque by Streptococcus mutans on dental surfaces under these model conditions. The enamel was colonized with regular cell clusters showing a globular appearance. The globules coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…Although various combinations of saliva and serum have been reported in the literature, 18,19 a 1:1 ratio was used in our study to simulate the oral conditions. Serum within the oral cavity is present in the form of gingival crevicular fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Although various combinations of saliva and serum have been reported in the literature, 18,19 a 1:1 ratio was used in our study to simulate the oral conditions. Serum within the oral cavity is present in the form of gingival crevicular fluid.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that 'a mixed-culture chemostat is a suitable system for studying the effects of nutrients on microbial populations; however, unlike the 'artificial mouth' system, the chemostat model does not account for the spatial arrangement o f dental plaque' since bacteria are studied in suspension and not as a biofilm on the tooth sur face. Zampatti et al [1994] used S. mutans in a mouth model based on Noorda et al [1985] to test the efficacy of anti plaque agents. Their model involved the use of bovine teeth to study plaque formation, but no attempt was made to study dental caries.…”
Section: Discussionmentioning
confidence: 99%
“…Artificial mouth models using enamel or hydroxyapatite surfaces Colonization, biofilm metabolism, effects of antimicrobial compounds Russell and Coulter, 1975;Coulter and Russell, 1976;Dibdin et al, 1976;Sissons and Cutress, 1987;Zampatti et al, 1994;Sissons, 1997 Keevil et al, 1987;Herles et al, 1994;Li and Bowden, 1994;Wolfaardt et al, 1994;Marsh, 1995;Møller et al, 1998;Heydorn et al, 2000;De Kievit et al, 2001;Neu et al, 2002 Fluidized bed environments and airlift reactors Biofilm structure; biotransformations Gjaltema et al, 1995;Tijhuis et al, 1996 Perfused biofilm fermenter Antimicrobial susceptibility; cell surface hydrophobicity; extracellular polymeric substances (EPS) production Gilbert et al, 1989;Allison et al, 1990aAllison et al, ,b, 1999Duguid et al, 1992a,b;Evans et al, 1994 Constant depth film fermenter Biofilm formation, ecology; effects of antimicrobials (including effects on oral malodor) Kinniment et al, 1996;Wilson, 1996;McBain et al, 2003a,b,c;Pratten et al, 2003 Sorbarod system Characterization of pure and mixed species biofilms; antimicrobial susceptibility; effects of cysteine on VSC (oral malodor) Hodgson et al, 1995;Budhani and Struthers, 1997;Foley and Gilbert, 1997;Gander and Gilbert, 1997;Gander and Finch, 2000;Maira-Litra´n et al, 2000;Greenman et al, 2002;Nelson et al, 2003;Spencer et al, 2003…”
Section: Biofilm System Applications Authorsmentioning
confidence: 99%